Transient epileptic amnesia - Anužytė , J. S.; Rutkauskaitė , G.; Mameniškienė , R. (Neurologijos seminarai, 2018)
Transient epileptic amnesia is an adult onset form of temporal epilepsy which is characterised by recurrent acute seizure-induced amnesia often accompanied by ongoing memory disturbances of autobiographical, topographical amnesia and accelerated long-term forgetting. The first case report of transient epileptic amnesia was described more than a hundred years ago. However, more extensively investigations of this type of epilepsy were started not long ago. In 1998 diagnostic criteria were formulated: 1) history of recurrent witnessed episodes of transient amnesia; 2) cognitive functions other than memory are judged to be intact during typical episodes by a reliable witness; 3) evidence for a diagnosis of epilepsy, provided by one or more of the following: (a) wake or sleep electroencephalography; (b) the co-occurrence of other seizure types (if their roughly concurrent onset and/or close association with episodes of transient amnesia suggested a connection); (c) a clear-cut response to anticonvulsant therapy. From case reports that are analysed in literature it is not difficult to summarise clinical characteristics: transient epileptic amnesia usually starts later in life, more often in men than in women; amnestic episodes are brief, recurrent and often occur upon waking; memory loss is usually mixed type with anterograde and retrograde amnesia; in 65% of patients amnesia is associated with gustatory or olfactory hallucinations, déjà vu, a brief period of unresponsiveness, automatisms; epileptiform abnormalities on electroencephalography were seen in 43% cases; although transient epileptic amnesia has an excellent response rate to anticonvulsant therapy, between episodes patients still suffer from accelerated long-term forgetting, remote memory impairment and topographical amnesia. Differential diagnostic of transient epileptic amnesia is diverse and diagnosis is usually inaccurate and overdue. Treatment with monotherapy often helps totally prevent recurrence of attacks. In the paper we review two case reports of patients with transient epileptic amnesia.
Keywords: transient epileptic amnesia; transient amnesia; temporal epilepsy; memory